Research Enterprise in Covid-19 Times: Establishing the New Normal - Peter G. Waterworth (Universitas Pendidikan Indonesia Kampus Serang, 2021)
What impact has the spread of the covid-19 virus had upon research programs in universities? The virus has been resistant to government measures to restrict its spread and the resulting health crisis has led to an economic crisis which is impacting every part of the global economy. Research enterprise has been affected in many ways particularly as research resources have been diverted into medical and strategic crisis response. This paper describes the impact of the pandemic in Australia on research departments of universities and analyses the implications of this impact for researchers and writers. It draws attention to the way research commissions from government departments and grants from research funding bodies are redirecting research funds to covid related projects and away from the tradition pre-covid priorities. Finally, it describes ways that research departments and individual researchers can adjust to the new normal in the research environment